Cooling dehumidification characteristics of two cooling systems applied in natural light plant factory in the rainy summer. Issue 3 (March 2020) - Zhang, Zhonghua; Zhong, Yuqi; Meng, Xiangzhen; Shi, Xiaocheng; Yang, Gukun; An, Wenting; Tian, Qinyu; Shi, Huixian
Abstract: In summer, it is easy to cause the plant to die in the natural light plant factory due to high temperature and high humidity. It is studied for the cooling dehumidification characteristics among various ways of cooling and dehumidification - water Energy- saving groundwater source heat pump cooling air treatment unit (ATU), wet curtain fan, mechanical ventilation, etc. in the semi-enclosed natural light plant factory in typical plum rain weather. The results show that, during the rainy season, the external environment is relatively low temperature. On a typical day, the average temperature is 28.10°C from 9:15 to 17:00 in daytime in the natural light plant factory with only mechanical ventilation. The indoor temperature is 31.1°C, and the average relative humidity is 81.61%, which can meet the needs of suitable temperature and humidity for cultivated crops. Compared with the normal opening of ATU, only the A area can save the operating cost of 337.34 yuan per day. Between 0:00 and 6:40 in the morning and 20:40 to 24:00 in the evening, the average relative humidity of the natural light plant with both mechanical and natural ventilation is 87.03%. Only mechanical ventilation is opened, and the relative humidity is 95.44%. Therefore, natural ventilation should be strengthened from night to next morning.